Policy Diversity on Lecturer Professionalism: A Literature Review of National, Institutional, and Global Policies - Hidayah, Jumatul; Antoni, Jono; Asha, Lukman; Warlizasusi, Jumira; Fakhruddin, Fakhruddin; Iqbal Ramdhani, Muhammad (International Journal of Education Research and Development, 2025)
The professionalism of lecturers is a crucial factor in ensuring the quality of higher education. Various policies have been implemented at various levels—national, institutional, and global—to regulate and improve the professionalism of lecturers. This article aims to systematically examine various forms of policies that contribute to the formation of lecturer professionalism. The data in this research were analyzed using a thematic approach by reviewing and coding relevant literature, policies, and reports from 2015–2024 to identify patterns in how different policies affect lecturer professionalism. The results of the study show that the diversity of policies reflects the dynamics of higher education needs that continue to develop, ranging from certification demands, tridharma performance, and internationalization of education to sustainable development. This article emphasizes the importance of synergy between national policies, institutional strategies, and adaptation to global trends to support lecturer professionalism holistically.